Washout and Awakening Times after Inhaled Sedation of Critically Ill Patients: Desflurane Versus Isoflurane - Daume, Philipp (J Clin Med, 2021)
In recent years, inhaled sedation has been increasingly used in the intensive care unit (ICU). The aim of this prospective, controlled trial was to compare washout and awakening times after long term sedation with desflurane and isoflurane both administered with the Mirus™ system (TIM GmbH, Koblenz, Germany). Twenty-one consecutive critically ill patients were alternately allocated to the two study groups, obtaining inhaled sedation with either desflurane or isoflurane. After 24 h study sedation, anesthetic washout curves were recorded, and a standardized wake-up test was performed. The primary outcome measure was the time required to decrease the endtidal concentration to 50% (T50%). Secondary outcome measures were T80% and awakening times (all extremities moved, RASS −2). Decrement times (min) (desflurane versus isoflurane, median (1st quartile—3rd quartile)) (T50%: 0.3 (0.3–0.4) vs. 1.3 (0.4–2.3), log-rank test P = 0.002; P80%: 2.5 (2–5.9) vs. 12.1 (5.1–20.2), P = 0.022) and awakening times (to RASS −2: 7.5 (5.5–8.8) vs. 41.0 (24.5–43.0), P = 0.007; all extremities moved: 5.0 (4.0–8.5) vs. 13.0 (8.0–41.25), P = 0.037) were significantly shorter after desflurane compared to isoflurane. The use of desflurane with the Mirus™ system significantly shortens the washout times and leads to faster awakening after sedation of critically ill patients.